Spatial location of indomethacin associated with unimeric amphiphilic carrier macromolecules as determined by nuclear magnetic resonance spectroscopy. (11th February 2016) - Orban, David E.; Moretti, Alysha; Uhrich, Kathryn E.
Abstract: A combination of nuclear magnetic resonance (NMR) techniques including, proton NMR, relaxation analysis, two‐dimensional nuclear Overhauser effect spectroscopy, and diffusion‐ordered spectroscopy, has been used to demonstrate the spatial location of indomethacin within a unimolecular micelle. Understanding the location of drugs within carrier molecules using such NMR techniques can facilitate rational carrier design. In addition, this information provides insight to encapsulation efficiency of different drugs to determine the most efficient system for a particular bioactive. This study demonstrates that drugs loaded by the unimolecular amphiphile under investigation are not necessarily encapsulated but reside or localize to the periphery or interfacial region of the carrier molecule. The results have further implications as to the features of the unimolecular carrier that contribute to drug loading. In addition, evidence of drug retention associated with the unimolecular surfactant is possible in organic media, as well as in an aqueous environment. Such findings have implications for rational carrier design to correlate the carrier features to the drug of interest and indicate the strong retention capabilities of the unimolecular micelle for delivery applications. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Unimeric amphiphilic carrier molecules are shown to encapsulate approximately four indomethacin molecules per carrier, as demonstrated using nuclear magnetic resonance spectroscopy techniques. The indomethacin molecules preferentially localize to the interfacial region and are retained in organic and aqueous conditions.